Development of Wattpad-Based Learning Media on Materials Avoiding Promiscuity in Secondary Schools - Putriani, Putriani; Riawarda, A.; Makmur, Makmur; Arisal, Andi (South Sulawesi Education Development (SSED), 2024)
This research aims to develop and evaluate the effectiveness of Wattpad-based learning media on the material